Morphological and morphometric study of the androgenetic alopecic scalp using two‐ and three‐dimensional analysis comparing regional differences. (1st June 2014) - Kim, J.N.; Lee, J.Y.; Shin, K.J.; Gil, Y.C.; Koh, K.S.; Song, W.C.
Summary: Background: Androgenetic (male‐type) alopecia (AGA) is caused by genetic and androgenetic effects. The progression of baldness results in smaller hair papillae, thinner hair and a shortened hair cycle. Alopecia occurs mainly in the frontal region and, to a lesser extent, in the occipital region. Objectives: The morphological differences in the hair follicular units between the alopecic frontal scalp and the vertex and occipital regions were compared using cross‐sectional histology and three‐dimensional reconstruction. Methods: Skin specimens were obtained from the frontal, vertex and occipital regions of 24 male human cadavers with fully progressed AGA, and from the frontal region of 32 normal cadaveric scalps. These specimens were fixed, processed using routine histological methods, serially sectioned at a thickness of 10 μm and then stained with Masson's trichrome. The serial sections were reconstructed three‐dimensionally using 'Reconstruct' software. Results: The ratios between the numbers of terminal and vellus hairs in the frontal and occipital regions in the AGA scalps were 0·2 : 1 and 3·5 : 1, respectively. Almost all of the hair follicles in the frontal region were vellus hair follicles. The sebaceous gland and arrector pili muscle were larger in the frontal region than in the occipital region. Conclusions: The morphology of the AGA scalp has been characterized. The terminal‐to‐vellus hair ratio in the occipital (normal) region was different from that in the frontal (alopecic) region. Moreover, sebaceous glands were larger in the frontal alopecic region than in the occipital region. These larger glands may be associated with other dermatological pathologies, such as seborrhoeic dermatitis.